STRATEGI IKATAN PELAJAR NAHDATUL ULAMA (IPNU) DALAM MENANGGULANGI KENAKALAN REMAJA DI KOTA PINRANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem of this research is what is the strategy of the Nahdatul Ulama Student Association in tackling juvenile delinquency in Pinrang City. Then it is formulated into several sub-problems, namely: What is the role of the Nahdatul Ulama Student Association in Overcoming Juvenile Delinquency in Pinrang City? What is the Strategy of the Nahdatul Ulama Student Association in Overcoming Juvenile Delinquency in Pinrang City? This type of research is qualitative using a da'wah management approach. The data sources for this research were primary data sources and secondary data sources. The informants included the Chairperson of the Pinrang branch of IPNU, the General Secretary of IPNU, IPNU Daily Executives, and Members of IPNU. The data collection method is (Observation) observation (Interview) and documentation. Then the data processing techniques used are data reduction, data display, comparative analysis, and drawing conclusions. The results showed that the Pinrang branch of the IPNU played a very important role in fostering the morale of Pinrang City Youth amidst technological developments and promiscuity. Which has been a form of moral development for generations by conducting cadre as a form of IPNU successor relay. and has a superior program, namely an anti-drug workshop. Carrying out moral development for generations Pinrang City has strengths, weaknesses, and opportunities from an internal and external perspective. The implications of this research are: 1). It is hoped that IPNU administrators in Pinrang City will always continue to be committed to fostering juvenile delinquency among children, bearing in mind that children are the next generation of hope for the nation. 2). It is hoped that the government of Pinrang City can work together with the board of IPNU Pinrang City in fostering children's morals in accordance with the Al-Quran and Ahlu Sunnah Wal-jama'ah. For the sake of the realization of easy intellectual and religious generations.